Lead (Pb) isotopic fingerprinting and its applications in lead pollution studies in China: A review - Cheng, Hefa; Hu, Yuanan (Environmental pollution (1987), 2010)
As the most widely scattered toxic metal in the world, the sources of lead (Pb) observed in contamination investigation are often difficult to identify. This review presents an overview of the principles, analysis, and applications of Pb isotopic fingerprinting in tracing the origins and transport pathways of Pb in the environment. It also summarizes the history and current status of lead pollution in China, and illustrates the power of Pb isotopic fingerprinting with examples of its recent applications in investigating the effectiveness of leaded gasoline phase-out on atmospheric lead pollution, and the sources of Pb found in various environmental media (plants, sediments, and aquatic organisms) in China. The limitations of Pb isotopic fingerprinting technique are discussed and a perspective on its development is also presented. Further methodological developments and more widespread instrument availability are expected to make isotopic fingerprinting one of the key tools in lead pollution investigation. This review presents an overview of the principles, applications, and limitations of Pb isotopic fingerprinting in lead pollution investigation, and provides a perspective on its future development.